Depressed classes of India / introduction by Rajendra Singh Vatsa (New Delhi, 1977)
The depressed classes have been the weakest consti tuent of the Indian social structure. Their origin is shrouded in past mystery. According to a popular theory, chiefly propounded by western scholars, they are the descendant of the aboriginal inhabitants of the northern and central Indian regions, attacked, conquer ed and enslaved centuries ago by the Aryan invaders. But in south India it was only later on when the Brah manic religion spread there, that all those aboriginals or Adi-Dravidians, who agreed to embrace it, were included as Shudras. Fresh inclusions of such people into the Brahmanic fold led to additions of new Shudra sub castes. Dr. B.R. Ambedkar, a politician, intellectual, and himself a member of the depressed classes, argued that the Shudras were Aryans and belonged to the Kshatriya class.
Keywords: Shudras